2024
DOI: 10.1186/s12909-024-05174-y
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness and gender dynamics in surgical specialties: a comparative analysis of French medical graduates (2017–2022)

Saadé Saadé,
Arnaud Delafontaine,
Johann Cattan
et al.

Abstract: Background French medical graduates undertake a national examination at the end of their studies with a subsequent national ranking. Specialty is then chosen by each candidate according to their ranking. This study aims to describe the attractiveness of surgical specialties and the evolution of the male-female distribution among French medical graduates (FMG) from 2017 to 2022. Methods Our database included the candidates’ ranking, sex and choice o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In our study, the majority of students perceived a career in a specialized care setting (both inpatient and outpatient) as most attractive throughout the observation period and the attractiveness of outpatient gynecology/pediatrics increased significantly (mainly observed in the Med General education track). These findings are consistent with the literature, although a direct comparison is not possible due to differences in the specialty definition between studies [ 24 , 33 , 34 ]. Moreover, longitudinal studies found that the most stable career intentions were general practice and internal medicine and the least stable were pediatrics and obstetrics-gynecology [ 22 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the majority of students perceived a career in a specialized care setting (both inpatient and outpatient) as most attractive throughout the observation period and the attractiveness of outpatient gynecology/pediatrics increased significantly (mainly observed in the Med General education track). These findings are consistent with the literature, although a direct comparison is not possible due to differences in the specialty definition between studies [ 24 , 33 , 34 ]. Moreover, longitudinal studies found that the most stable career intentions were general practice and internal medicine and the least stable were pediatrics and obstetrics-gynecology [ 22 , 24 ].…”
Section: Discussionsupporting
confidence: 91%